Soybean biorefinery with residues exploitation : process assessment - Pretto, Cristine De (2016)
Soybean seed is a renewable feedstock and the production process of soybean meal and soybean refined oil generates residues that can be exploited, in such a way that the biorefinery concept can be applied to this production process. For this reason, this work aimed to analyse the employment of the biorefinery concept to a soybean crushing and refining facility, exploiting applications for the residues generated during the process. For that, first, information and data from literature about the traditional manufacture process of soybean meal and refined soybean oil were collected and the residues produced during this process were identified. Once the residues were recognized, data in academic literature about possible applications for the residues were collected. Next, the traditional process for producing soybean refined oil and defatted meal was simulated using a commercial simulator. The amounts of residues generated and energetic requirements were calculated. The amount of residues generated during soy protein concentrate (SPC) and soy protein isolate (SPI) process production were also obtained by simulations of these processes. Following, an application for each residue (except for SPI residues) was simulated in the same software and the results were analysed. It was verified that soybean straw and hulls could fulfill the energetic demand of the crushing, refining and biodiesel production process and even a surplus of electricity could be generated, especially when biodiesel was also used as a boiler fuel. Four residues from refining process are generated: gums, soapstock, spent bleaching earth and deodorizer distillate. From gums, it is possible to produce lecithin. From soapstock and spent bleaching earth, biodiesel can be generated, although it generates more residues and consumes more steam than the production of biodiesel from degummed oil. From deodorizer distillate, it is possible to concentrate tocopherols, which is an antioxidant and can be sold for its antioxidant properties. Soybean molasses generated during the concentration of proteins from soybean meal can also be used for electrical energy production.